Probing heat generation and release in a 57.5 A h high-energy-density Li-ion pouch cell with a nickel-rich cathode and SiOx/graphite anode. Issue 3 (22nd December 2021) - Qi, Xiaopeng; Liu, Bingxue; Yun, Fengling; Wang, Changhong; Wang, Rennian; Pang, Jing; Tang, Haibo; Quan, Wei; Zhang, Qiang; Yang, Man; Wu, Shuaijin; Wang, Jiantao; et al.
Abstract : This study clarifies the heat generation and release of a 57.5 Ah HED (266.9 W h kg −1 ) Li-ion cell with a nickel-rich cathode and SiO x /graphite anode. Significant heat accumulation and delayed heat release effects in large-format cells are uncovered. Abstract : The electrochemical performance, reliability, and safety of Li-ion cells depend on thermal management. However, the heat generation mechanisms and release characteristics of large-format high-energy-density (HED) Li-ion cells, a prerequisite for an efficient battery thermal management system (TMS), remain unclear. This study clarifies the heat issues of a 57.5 Ah HED (266.9 W h kg −1 ) Li-ion cell with a promising material couple of nickel-rich cathode and SiO x /graphite anode. Both reversible entropic heat and irreversible polarization heat at different discharge rates are unraveled. While charge transfer and mass transport dominate the total polarization heat, the contribution from the ohmic effect and surface impedance increases with discharge rates. Polarization heat also increases consistently with lowering SOCs because of the increasing mass transport overpotential. In particular, the abrupt increase of heat generation at a SOC below 25% may be due to the leveraged discharge rate of SiO x caused by the mismatch of the voltage windows of graphite and SiO x . Moreover, the isothermal calorimetry study uncovers the significant heat accumulation and delayed heat release effects of large-format cells, which could cause undetectable but dangerous internal temperature rise at high discharge rates. Findings obtained in this study could guide the rational design of HED cells and TMS optimization.